Preterm infant feeding knowledge, attitudes, and practices amongst health practitioners at tertiary hospitals in Capricon District, Limpopo Province, South Africa - Ralebapa, Khomotso (My University, 2024)
Introduction: Preterm infant feeding is the cornerstone for growth and development, and yet not prioritized by health practitioners. Aim: This study aims to determine preterm infant feeding, knowledge, attitudes, and practices amongst health practitioners at tertiary hospitals in Limpopo province, South Africa. Methodology: The study was conducted among 40 health practitioners working at the neonatal unit at Mankweng Tertiary Hospital. The sample size was calculated using the Morgan and Krejci formula, however due to the small sample size, the total population sample methodology was employed. The sample included 16 Medical practitioners and 24 registered nurses. The study complied to all ethical considerations. Data on the knowledge, attitudes and practice amongst health practitioners was collected using a structured self-administered questionnaire. Data analysis: Statistical Package for the Social Sciences (SPSS) version 29 was used to analyse the data. Continuous variables were presented using minimum, maximum, mean and standard deviation. Categorical variables were presented with frequencies and percentages. Knowledge and practice questions were allocated one point for every correct answer and zero for a wrong answer. The overall knowledge and practice were interpreted using Bloom cut-off, and presented as maximum, minimum, mean and standard deviation. The attitudes questions were analysed using the attitudes score, and the overall attitudes score was calculated and presented as maximum, minimum, mean and standard deviation. The relationship between the socio-demography of health practitioners and the knowledge, attitudes and practice (KAP) was analysed using Pearson chi-square. The strength of the relationship was determined using Pearson’s correlation coefficient. P-value of less than 0.05 was considered as significant. Results of the study: The majority (77%) of health practitioners had moderate knowledge, mean knowledge score of 48%, 88% of health practitioners had a positive attitude, with the mean attitudes score of 89.9%, and 58% of health practitioners obtained a moderate practice, mean score of 64.7%, on preterm infant feeding. There was a significant relationship between registered nurses and knowledge of preterm infant feeding (p=0.003), and years of experience of registered nurses and knowledge (p=0.046). Additionally, there was a significant relationship (p=0.031) between registered nurses’ years of working with preterm infant and their knowledge on preterm infant feeding. There was no statistically significant association between socio-demographic characteristics and the overall KAP variables. Conclusion: Health practitioners at tertiary hospitals in Limpopo obtained a moderate score on knowledge, positive attitudes, and a moderate score on practice on preterm infant feeding, and there was no association between sociodemographic and KAP variables.
Thesis (M.Sc. (Dietetics)) -- University of Limpopo, 2024
Keywords: Preterm; Knowledge; Attitudes; Practice; Premature infants; Infant formulas; Bottle feeding